The Characteristics of The General Population in Medan Undergoing Lung Cancer Screening with NARU - Febiyanti, Mica; Tarigan, Setia Putra; Soeroso, Noni Novisari; Eyanoer, Putri Chairani (CoinReads Media Prima, 2024)
Introduction: Indonesia introduced the NARU lung cancer screening form to assess individual risk levels for lung cancer, classifying them as low, medium, or high risk. This study aimed to analyze the characteristics of low, medium and high risk groups in Medan city. Methods: A quantitative, descriptive cross-sectional design was used, involving 100 individuals from primary health care facilities across 11 areas, who were evaluated using the 9-question NARU form. Evaluation concluded the individuals into low, medium, and high risk of lung cancer. Results: The majority of the responded high-risk group for lung cancer, the majority were males aged 45-65 years. They had no personal or family history of cancer but were active smokers, worked in carcinogenic environments, and did not live in homes or environments with carcinogenic risks. Additionally, they had a history of COPD and/or TB. In the moderate-risk group, both males and females aged 45-65 years were included, with no personal or family cancer history. They were passive smokers, did not work in carcinogenic environments, and did not live in homes or environments with carcinogenic risks. None had a history of COPD or TB. In the low-risk group, the majority were females under 45 years. They had no personal or family cancer history, were non-smokers, did not work in carcinogenic environments, and did not live in homes or environments with carcinogenic risks. They also had no history of COPD or TB. Conclusion: The study concluded that in Medan, 48% of the population fell into the moderate-risk group for lung cancer, while 31% were in the low-risk group, and 21% were classified as high risk.